57% of RCTs of cardiovascular nursing interventions show that they improve at least one outcome for secondary prevention patients; optimum intervention strategy unclear. Issue 4 (30th July 2010) - Gallagher, Robyn
Abstract : Commentary on: Allen JK Dennison CR . Randomized trials of nursing interventions for secondary prevention in patients with coronary artery disease and heart failure: systematic review . J Cardiovasc Nurs 2010 ;25 :207 –20 .